Disparate population and holobiont structure of pocilloporid corals across the Red Sea gradient demonstrate species‐specific evolutionary trajectories. Issue 9 (3rd March 2023) - Buitrago‐López, Carol; Cárdenas, Anny; Hume, Benjamin C. C.; Gosselin, Thierry; Staubach, Fabian; Aranda, Manuel; Barshis, Daniel J.; Sawall, Yvonne; Voolstra, Christian R.
Abstract: Global habitat degradation heightens the need to better understand patterns of genetic connectivity and diversity of marine biota across geographical ranges to guide conservation efforts. Corals across the Red Sea are subject to pronounced environmental differences, but studies so far suggest that animal populations are largely connected, excepting evidence for a genetic break between the northern‐central and southern regions. Here, we investigated population structure and holobiont assemblage of two common pocilloporid corals, Pocillopora verrucosa and Stylophora pistillata, across the Red Sea. We found little evidence for population differentiation in P. verrucosa, except for the southernmost site. Conversely, S. pistillata exhibited a complex population structure with evidence for within‐reef and regional genetic differentiation, in line with differences in their reproductive mode ( P. verrucosa is a broadcast spawner and S. pistillata is a brooder). Analysis for genomic loci under positive selection identified 85 sites (18 of which were in coding sequences) that distinguished the southern P. verrucosa population from the remainder of the Red Sea population. By comparison, we found 128 loci (24 of which were residing in coding sequences) in S. pistillata with evidence for local adaptation at various sites. Functional annotation of the underlying proteins revealed putative roles in the response to stress, lipid metabolism, transport, cytoskeletal rearrangement, and ciliary function (among others). Microbial assemblages of both coral species showed pervasive association with microalgal symbionts from the genus Symbiodinium (former clade A) and bacteria from the genus Endozoicomonas that exhibited significant differences according to host genotype and environment. The disparity of population genetic and holobiont assemblage patterns even between closely related species (family Pocilloporidae) highlights the need for multispecies investigations to better understand the role of the environment in shaping evolutionary trajectories. It further emphasizes the importance of networks of reef reserves to achieve conservation of genetic variants critical to the future survival of coral ecosystems.